BRIDGING ECOLOGY AND ECONOMY THROUGH ISLAMIC ETHICS OF STEWARDSHIP - Gayatri, Erin (Jurnal Ekonomi & Studi Pembangunan, 2017)
Even though itâ€™s originated from the same word oikos, literally means house, the discussion about ecological economics tend to be located in the opposite enterprises. In the abstract level, the discussions about ecology focus on the sustainability and conservation of biodiversity while the economic discourses lean toward the development and growth. Furthermore, many environmentalists accuse the thriving economic growth and development lead to ecological calamity. On the other hand, the economics technocrats suspiciously perceive the environmentalist as anti-growth and development. Even though Islamic classical literatures do not contain the word economy and ecology, yet the discourse about maintaining the limited resources of the earth for human development and growth have already and continuously scrutinized.Â  Reflecting from the situations, this paper tries to bridge the tense relation between ecology and economy by elaborating the Islamic ethics of stewardship into both field studies. In doing so, the discussion shall begin by examining the field of ecology and economy in order to find common ground between the two. The ways we comprehend ecology in Islamic perspectives helps us to refine our understanding and practices in Islamic economics, and vice versa, this â€œgreenâ€ Islamic economy might contribute to enhance our environmental situations.